Barriers and facilitators to cooking from 'scratch' using basic or raw ingredients: A qualitative interview study. (1st December 2016) - Lavelle, Fiona; McGowan, Laura; Spence, Michelle; Caraher, Martin; Raats, Monique M.; Hollywood, Lynsey; McDowell, Dawn; McCloat, Amanda; Mooney, Elaine; Dean, Moira
Abstract: Background: Previous research has highlighted an ambiguity in understanding cooking related terminology and a number of barriers and facilitators to home meal preparation. However, meals prepared in the home still include convenience products (typically high in sugars, fats and sodium) which can have negative effects on health. Therefore, this study aimed to qualitatively explore: (1) how individuals define cooking from 'scratch', and (2) their barriers and facilitators to cooking with basic ingredients. Methods: 27 semi-structured interviews were conducted with participants (aged 18–58 years) living on the island of Ireland, eliciting definitions of 'cooking from scratch' and exploring the reasons participants cook in a particular way. The interviews were professionally transcribed verbatim and Nvivo 10 was used for an inductive thematic analysis. Results: Our results highlighted that although cooking from 'scratch' lacks a single definition, participants viewed it as optimal cooking. Barriers to cooking with raw ingredients included: 1) time pressures; (2) desire to save money; (3) desire for effortless meals; (4) family food preferences; and (5) effect of kitchen disasters. Facilitators included: 1) desire to eat for health and well-being; (2) creative inspiration; (3) ability to plan and prepare meals ahead of time; and (4) greater self-efficacy in one's cooking ability. Conclusions: Our findings contribute to understanding how individuals define cooking from 'scratch', and barriers and facilitators to cooking with raw ingredients. Interventions should focus on practical sessions to increase cooking self-efficacy; highlight the importance of planning ahead and teach methods such as batch cooking and freezing to facilitate cooking from scratch.